Número de gestas y su relación con sobrepeso y obesidad en gestantes que acuden al centro de salud Nº3, Loja - Granda Hualpa, Jhuliana Michelle (2020)
Overweight and obesity are defined as an abnormal or excessive accumulation of fat in the human body and during pregnancy these nutritional alterations are of great importance, since they determine high risk conditions, both for the pregnant woman and for the fetus. Therefore, the aim of this research work was to know the relationship between the number of gestations with overweight and obesity in pregnant women; who go to the health center No. 3 of the city of Loja, during the period of January 2013 to December 2017. The methodological design was based on a descriptive, analytical, quantitative, and prospective cross-sectional approach. It counted with the participation of 622 women in gestation period who attended the health center No. 3 in a certain period of time. As research techniques were used surveys and the review of medical records. As an instrument was used the sheet A 051 of the Ministry of Public Health, and the data were tabulated through the SPSS v. 22. As the main results of this research it was found that pregnant women who attended the health center No. 3 of the city of Loja are large multiparous in 40%. Regarding to the body mass index, we noticed that the nutritional status of the pregnant women are mostly in Obesity Grade II with 51.6%. And as for the relationship of these two variables, it was found that large multiparous women are 0.5 times more likely to be overweight or obese in their pregnancy (OR: 1.526, CI: 95%, 1.318-1.767). In addition, there is a significant difference (Chi2 = 30,839a, p = 0,000); which expresses that there is a statistically significant relationship between the number of feats and overweight and obesity. Therefore, it is concluded that the number of feats does influence overweight and obesity during pregnancy; we have also come to the conclusion that the majority of pregnant women of the health center No. 3 of Loja have a high parity and have a high percentage of overweight and obesity. For this reason, it is necessary the support and attention of the health personnel. Keywords: Overweight, obesity, pregnancy, number of feats, large multiparous.